2021
DOI: 10.1123/iscj.2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Youth Football Coaches’ Perception of Concussion Safety in American Youth Football and Their Experiences With Implementing Tackling Interventions

Abstract: Due in part to concern about the potential long-term effects of concussion and repetitive head injuries in football, some programs have implemented tackling interventions. This paper explores youth football coaches’ perception of football safety and their experiences implementing these interventions aimed at athlete safety. Using a qualitative approach, coaches were interviewed by means of a semi-structured protocol that covered: (a) demographics; (b) background and experiences with contact sports; (c) perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This is important as flag football participation has increased over the past decade with the promotion of its safety as an alternative to tackle football, even as data on head impact exposure between tackle and flag football continue to be limited and contradictory, suggesting that each type of football has its own inherent risks. 10 , 12 , 13 , 16 , 17 , 20 While we do not have a league-specific injury pattern data that could affect participation enrollment in this study, we presumed that these patterns would correlate with national data. Furthermore, injury rates for most of the leagues that we recruited from have been described previously by Peterson et al 12 as our study recruited from the same locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important as flag football participation has increased over the past decade with the promotion of its safety as an alternative to tackle football, even as data on head impact exposure between tackle and flag football continue to be limited and contradictory, suggesting that each type of football has its own inherent risks. 10 , 12 , 13 , 16 , 17 , 20 While we do not have a league-specific injury pattern data that could affect participation enrollment in this study, we presumed that these patterns would correlate with national data. Furthermore, injury rates for most of the leagues that we recruited from have been described previously by Peterson et al 12 as our study recruited from the same locations.…”
Section: Discussionmentioning
confidence: 99%
“…Age limits to tackling have also been proposed, but youth football coaches have reported that learning tackling at a younger age better prepares athletes for playing later in life, as athletes can practice proper blocking and tackling techniques. 2,16 The American Academy of Pediatrics Council on Sports Medicine and Fitness have also discussed the potential costs of these age limits to tackling, including concern about lack of early exposure leading to greater severity of injuries when tackling is finally introduced. 5 Even with these national recommendations, there have been few studies examining tackle and flag football injuries in youth participants.…”
mentioning
confidence: 99%